MORPHOLOGICAL, PHYSICAL AND CHEMICAL CHARACTERIZATION OF SOILS REPRESENTING THE CLAY PLAINS OF THE SUDAN - P.W., Marchelo-d’Ragga; P.K., Deng, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The morphological features and physico-chemical properties of seven pedons representing the major soil types in the clay plains of Sudan were studied. Soil profiles were dug in the clay plains of Sudan and seven profiles were selected in a transect from East of Rahad River, across Gezira, and west of the White Nile. The objectives were to investigate morphological features and physico-chemical characteristics of these soils, forms and soil samples according to genetic horizons. Twenty-eight soil samples and four genetic horizons were selected from the seven soil profiles; and were selected for morphological physical and chemical characteristics. The results showed that, these soils are deep with more than 150 cm depth, cracking surface, very dark grey 10YR3/1 to dark brown and well drained. Soil texture was clay with variation in relation to physiography (40-70), soil consistency was firm to very friable, and pH was alkaline 7.2 to 8.9 with low to high organic carbon of 0.03 to 1.3% and high CEC (53-89) c mol (p+) kg-1). The organic carbon content and CEC were higher in Rahad and Gezira soils which might be due to the clay translocation and organic carbon content accumulation. These soils had high cation exchange capacities due to the high clay content. Also, most were alkaline, non – saline with ECe (0.2-2.1dS m-1) and non -sodic. The major pedogenic processes are illuviation/ colluviation. Similarity the colour and texture of most of the soils indicated the dominant influence of parent material. Most of the studied sites were classified as Chromic Haplotorrerts and Typic Haplotorrerts and soils in the area belong to the order Vertisols